Migração e trabalho : venezuelanos com formação acadêmica no Estado de Roraima - Oliveira, Pedro Carlos de Araújo (2020)
This work deals with the phenomenon of the migration of Venezuelan workers with academic formation for the state of Roraima, as well as the implications for their insertion in the labor market. It aims to analyze the migratory politics of the Brazilian State for the integration of the migrant ones through the use of the acquired, process of recognition and revalidation of academic titles.The study is a descriptive inquiry and of bibliographic survey, which exposes the relation between categories that wrap the phenomenon of migration and work. It uses revalidation data and recognition of academic degrees from the Plataforma Carolina Bori. For approach of the subject the inductive method was used, with the purpose of identifying singular elements to understand the phenomenon. The quantitative, qualitative and analytical methods were used in the proceedings of exposure and analysis of the content. It is identified that migrants with academic backgrounds have difficulties with the proceeding for recognition and revalidation of diplomas through the electronic platform and that the number of Venezuelan work contracts with a complete superior level is not proportional to the migrant contingent that has academic formation. It is concluded that for the State to guarantee the integration of migrant workers, it is not enough to inspect the formalization of employment contracts with qualified migrants and regularize documentation, but to create strategies capable of reducing inequality between the native population and those workers, under the principle of equity. As well as the identification of their skills and articulation with the private sector, in order to publicize opportunities in jobs and incentive policies to the development.